Enhancing Gaming Engagement through the Integration of Game Design Document and Finite State Machine: A Study on Optimizing Non-playable Character Responsiveness - Wiratama, Jansen; Rian; Evelin Johan, Monika; Santoso, Hari (AI Society & STMIK Indonesia, 2023)
Non-playable Character (NPC) is a prominent terminology within the gaming domain. While players do not directly control NPCs, their role significantly influences the gaming experience. Enhancing NPC responsiveness becomes imperative as NPCs' passive nature can lead to monotonous gameplay. To address this concern, a computational model, namely Finite State Machine (FSM), is implemented to elevate NPC responsiveness during interactions with the main characters, whether as adversaries or allies. This research uses the Game Design Document (GDD) methodology to design a survival horror-themed game. The resultant Survival Horror Game undergoes Alpha testing to validate its overall functionality and the successful integration of the FSM computational model. Findings indicate that enemy NPCs can pursue the main character from any position, with an average arrival interval of 68 seconds. Additionally, allied NPCs promptly respond when the main character approaches. Subsequently, the Beta testing results reflect an 80% average score interpretation based on percentage responses, implying the game's favorable suitability and acceptability on the Likert scale.